New-Born Screening for Spinal Muscular Atrophy: Results of a Latvian Pilot Study - Linda Gailite; Olga Sterna; Maija Konika; Aleksejs Isakovs; Jekaterina Isakova; Ieva Micule; Signe Setlere; Mikus Diriks; Madara Auzenbaha (MDPI AG, 2022)
New disease-modifying treatments have recently been approved for 5q spinal muscular atrophy (SMA) and early treatment has been associated with a better clinical outcome. Accordingly, new-born screening (NBS) for SMA should be implemented to ensure early diagnosis of affected individuals. The aim of this study was to determine the feasibility and usefulness of NBS for SMA in Latvia. Between February and November of 2021, 10,411 parents consented to participation in the study. DNA testing for the SMN1 exon 7 homozygous deletion was conducted using qPCR with fluorescent locked nucleic acid primers. In the first month of testing, reporting of results took up to a maximum of 17 days after samples arrived in the laboratory. However, following familiarisation with the procedure, the median report time was reduced to 11 days after birth. Forty cases required samples to be taken again due to poor quality of the isolated DNA transpiring from either the quality of the blood punch or manual mistakes during DNA isolation. The SMN1 exon 7 homozygous deletion was identified in two individuals, which was subsequently confirmed by multiplex ligation-dependent probe amplification. When a NBS sample is taken 48 to 72 h after birth and transported to the laboratory within two working days after collection according to legal requirements, DNA test results can be reported to healthcare professionals before the 12th day of life. Expansion of our SMA 5q NBS procedure to the whole of Latvia is feasible and would facilitate early diagnosis and result in more effective treatment. We strongly advocate that SMA is added to the national Latvia Recommended Uniform Screening Panel.